Development of Interactive Electronic Student Worksheets on Pythagorean Theorem Material to Support Students' Mathematical Reasoning in Junior High Schools - Elfariana, Rizma; Aisyah, Nyimas; Susanti, Ely (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
This study aims to develop Electronic Learner Worksheets (LKPD) or interactive E-LKPD on Pythagorean theorem material that meets valid, practical, and effective criteria. This development research was conducted at SMP Negeri 1 Parittiga with the research subjects of class VIII B students totaling 22 people. This research uses the RnD method with the Tessmer model which consists of two stages, namely preliminary studies and formative evaluation. This research is since there are still many secondary school students who have low mathematical reasoning skills on geometry topics, including the Pythagorean theorem. The results of this study indicate that the development of interactive E-LKPD on Pythagorean theorem material is categorized as valid and practical. The average validity value obtained was 89.46% with a very valid category. The characteristics of valid interactive E-LKPD on Pythagorean theorem material are (1) Presenting contextual problems that are close to the lives of students; (2) E-LKPD reflects the principles and characteristics of interactive E-LKPD; (3) E-LKPD guides students in constructing their own knowledge. Interactive E-LKPD on Pythagorean theorem exercise material is reviewed in terms of ease and benefits of use, time efficiency, and presentation attractiveness. The average practicality score obtained was 83.748% with a very practical category. The characteristics of the practicality of interactive E-LKPD are (1) Interactive E-LKPD is easy to use because the instructions provided are complete, clear, and the language is easy to understand; (2) E-LKPD processing time is efficient; (3) Commands and questions on E-LKPD are clear and easy to understand; (4) The appearance and color combination on E-LKPD is attractive; (5) Students are helped in understanding the concepts and material of the pythagorean theorem. Based on the results of interviews with teachers and students, interactive E-LKPD on Pythagorean theorem material facilitates students in learning and arouses students' interest in learning. Interactive E-LKPD on pythagorean theorem material can facilitate teachers and parents in conducting student learning activities anywhere and anytime. This research can be a meaningful experience and learning resource for students in learning geometry, especially about the Pythagorean theorem. Penelitian ini bertujuan untuk mengembangkan Elektronik Lembar Kerja Peserta Didik (LKPD) atau E-LKPD interaktif pada materi teorema Pythagoras yang memenuhi kriteria valid, praktis dan efektif. Penelitian pengembangan ini dilaksanakan di SMP Negeri 1 Parittiga dengan subjek penelitian siswa kelas VIII B yang berjumlah 22 orang. Penelitian ini menggunakan metode RnD dengan model Tessmer yang terdiri dari dua tahap, yaitu studi pendahuluan dan evaluasi formatif. Penelitian ini dilandasi karena masih banyak siswa sekolah menengah yang memiliki kemampuan penalaran matematis yang rendah pada topik geometri, termasuk teorema Pythagoras. Hasil penelitian ini menunjukkan bahwa pengembangan E-LKPD interaktif pada materi teorema Pythagoras dikategorikan valid dan praktis. Nilai rata-rata kevalidan yang diperoleh sebesar 89,46% dengan kategori sangat valid. Karakteristik E-LKPD interaktif yang valid pada materi teorema Pythagoras adalah (1) Menyajikan masalah kontekstual yang dekat dengan kehidupan peserta didik; (2) E-LKPD mencerminkan prinsip-prinsip dan karakteristik E-LKPD interaktif; (3) E-LKPD menuntun peserta didik dalam mengkonstruksi pengetahuannya sendiri. E-LKPD interaktif pada materi latihan soal teorema Pythagoras ditinjau dari segi kemudahan dan manfaat penggunaan, efisiensi waktu, dan kemenarikan penyajian. Rata-rata nilai kepraktisan yang diperoleh sebesar 83,748% dengan kategori sangat praktis. Karakteristik kepraktisan E-LKPD interaktif yaitu (1) E-LKPD interaktif mudah digunakan karena petunjuk yang diberikan lengkap, jelas, dan bahasanya mudah dipahami; (2) Waktu pengerjaan E-LKPD efisien; (3) Perintah dan pertanyaan pada E-LKPD jelas dan mudah dimengerti; (4) Tampilan dan perpaduan warna pada E-LKPD menarik; (5) Peserta didik terbantu dalam memahami konsep dan materi teorema pythagoras. Berdasarkan hasil wawancara dengan guru dan peserta didik, E-LKPD interaktif pada materi teorema Pythagoras memudahkan peserta didik dalam belajar dan membangkitkan minat belajar peserta didik. E-LKPD interaktif pada materi teorema pythagoras dapat memudahkan guru dan orang tua dalam melakukan kegiatan belajar siswa dimanapun dan kapanpun. Penelitian ini dapat menjadi pengalaman dan sumber belajar yang bermakna bagi peserta didik dalam mempelajari geometri khususnya mengenai teorema Pythagoras.